Global epidemiology of podoconiosis: A systematic review - Deribe, Kebede; Cano, Jorge; Trueba, Mei L.; Newport, Melanie J.; Davey, Gail (PLOS Neglected Tropical Diseases, 2018)
Author summary Podoconiosis is one of the Neglected Tropical Diseases, and causes painful and massive swelling of the lower legs. Despite the importance of the disease, its global distribution and epidemiology are poorly understood. We conducted a systematic review to assess the global epidemiology of podoconiosis. We found that podoconiosis was described to exist or be endemic in 32 countries, 18 from Africa, 3 from Asia and 11 from Latin America. Almost all prevalence data recorded corresponded to the African region. None of the Latin American countries reported prevalence data, although some countries are suspected to be endemic. We recommend that comprehensive podoconiosis control strategies such as promotion of footwear and personal hygiene are urgently needed in endemic countries in the African Region. Mapping, active surveillance and a systematic approach to the monitoring of disease burden must accompany the implementation of podoconiosis control activities.